Cidades resilientes, áreas verdes e adaptação às mudanças climáticas: uma contribuição ao cadastro ambiental urbano no município de Barcarena–Pa - PAIVA, Bárbara Souza (Universidade Federal do Pará, 2025)
This research aims to contribute to the discussion on resilient cities adapted to climate change in the face of global warming and El Niño. In this context, a strategic resource for addressing this reality is the use of green areas as nature-based solutions, due to their environmental and social benefits. This study analyzes land use planning, vegetation, alignment of environmental policies, the municipal Master Plan, the institutionalization of the 2030 Agenda for Sustainable Development's 17 Sustainable Development Goals (SDGs 11, 13, and 15), and adaptation to the New Urban Agenda adopted by the management of the municipality of Barcarena, PA. To do so, a methodology of systematic literature review was employed on urban planning, environmental management, green areas, nature-based solutions, environmental legislation, global and local agendas, and the theme of resilient cities in adaptation and mitigation to climate change. In order to understand the territory, the study produced primary data through the mapping of Land Use/Land Cover (LULC) in the thirty neighborhoods of the municipality and its surroundings (approximately 3 km) between 2016 and 2023. Remote sensing techniques and geoprocessing were used, processed in Google Earth Engine and QGIS software for spatial analysis, statistics, cartographic productions, graphs, and area calculations. Current urbanized area data show that vegetation has decreased and occupies 144.56 km2 (54% of the total area). Hydrography remained stable at 57.48 km2 (representing 22% of the total). Exposed soil increased to 26.22 km2 (10%). The urbanized area grew and occupies 17.62 km2 (7%). The current industrial-mining-port complex covers 18 km2 (7%). Regarding the 30 neighborhoods, current data shows that vegetation has decreased and occupies 21.36 km2 (41.51% of the total area). The urbanized area expanded and occupies 18.94 km2 (36.80%). Exposed soil increased to 11.15 km2 (21.67%). Meanwhile, hydrography remained unchanged at 0.01 km2 (0.02%). The study reveals a Vegetation Coverage Index (VCI) of 10.97%, indicating a decline in greenery, and low thermal comfort with the Vegetation Coverage Heat Index (VCHI) at around 9.66 m2/inhabitant, has heat islands. The research proposes as a product: data, maps, and methodology for the elaboration of the Urban Environmental Registry, to contribute to the alignment of municipal management with the State Plan for the Recovery of Native Vegetation and with the Decade of Ecosystem Restoration. It aims to be a tool to aid in future environmental zoning and the next Master Plan Review, with actions focused on the city's resilience, in the face of worsening climate crisis, aiming to contribute to the promotion of urban environmental quality and quality of life, for local sustainable development.